Effect of diffusion oxygen enrichment on soot formation in coflow diffusion flames of gasoline-surrogate fuel doped with ethanol. (15th November 2022) - Hua, Yang; Xiang, Xingwei; Qian, Yejian; Meng, Shun; Ye, Bin
Highlights: Combined effect of diffusion oxygen enrichment and ethanol addition to gasoline on soot was investigated numerically. The dominant mechanism of particle mass growth after ethanol addition does not change with the increasing oxygen concentration. Inhibition of ethanol addition and promotion of diffusion oxygen enrichment on soot attribute to PAH condensation and HACA, respectively. Coupling effect between oxygenated fuel and diffusion oxygen is strongest in the surface growth. Ethanol addition and diffusion oxygen enrichment have opposite effect on particle oxidation. Abstract: The combined effect of ambient oxygen enhancement and oxygenated fuel addition is expected to improve combustion efficiency and control soot formation. In this work, the effect of diffusion oxygen enrichment on soot formation and the particle dynamics mechanism in coflow diffusion flames of gasoline-surrogate doped with ethanol were investigated numerically. The results showed that the peak temperature and SVF of ethanol-gasoline flames increase linearly with the increase of diffusion oxygen concentration, while the ethanol addition reduces the peak temperature and SVF. The action mechanism of diffusion oxygen enrichment on final soot formation is the result of the competition between residence time and particle dynamics, while the action mechanism of ethanol addition is the combined effect of residence time and particle dynamics. From the perspective of particle dynamics, the dominant mechanism of particle growth in gasoline flame changes with the increase of diffusion oxygen concentration. When the oxygen concentration exceeds 25%, HACA gradually replaces PAH condensation as the main mechanism of particle mass growth. However, after adding ethanol, HACA is always the dominant mechanism of particle mass growth and does not change with the increasing oxygen concentration. The inhibition of ethanol addition on soot is mainly achieved by reducing the PAH condensation rate, while the promotion of diffusion oxygen enrichment on soot is largely attributed to the increasing temperature and HACA rate. In addition, there is a coupling effect between the oxygenated fuel addition and the diffusion oxygen enrichment on the inhibition of particle dynamics. The coupling effect is strongest in the surface growth of particles, and is further enhanced with the increasing ethanol ratio and oxygen concentration. Ethanol addition and diffusion oxygen enrichment do not change the dominant role of O2 oxidation in particle oxidation, but they have opposite effect on particle oxidation.